Bone augmentation by replica-based bone formation. Issue 11 (November 2020) - Draenert, M.E.; Martini, C.; Watts, D.C.; Draenert, K.; Wittig-Draenert, A.
Abstract: Objective: The sources of iliac crest bone grafts are limited. Alternatives are evaluated due to the progress in biomaterial sciences. Synthetical hydroxyapatite (HA), ß-tricalcium phosphate (ß-TCP) or biphasic compounds, or even a mélange of HA and ß-TCP will replace bovine ceramics. The goal is maintenance of replica-based-bone formation (RBBF) for bone augmentation. Methods: 2 female and 2 male patients between 41 and 73 years with 5 sinus elevations were evaluated. Sinus elevations with lateral fenestration, trapezoidal-muco-periosteal flaps and filling with micro-chambered beads (1.5 mm) was performed. A porcine-collagenous membrane and the refixated flap covered the defect. A biopsy program over 20 months was confirm confirm the maintenance of the newly formed bone. Results: A fast bone formation was pronounced. The biopsies revealed mature lamellar bone and full osseointegration of the ß-TCP implant. The biopsy after 20 months showed compact bone with osseointegration of minor rests of the ceramic implant. The defect revealed a mature bone stock already after 5 weeks. Significance: The introduction of the replica-based-bone formation (RBBF) around micro-chambered beads will change the paradigm of bone augmentation. The next step of the ongoing study has to redefine the interval for implant insertion. The clinical approach confirms the breakthrough to primary mature lamellar bone formation and will permit reduction of placement time for a dental implant.